Student perceptions of decision mathematics and legitimate mathematical practice. (27th April 2017) - Ward-Penny, Robert
Abstract: Decision mathematics is at present the least established and arguably the most contested strand of applied mathematics within the British A-level mathematics and further mathematics qualifications. This article presents data from a study comprising 10 A-level further mathematics candidates who chose as a cohort to study a second module of decision mathematics. The students described their developing attitudes towards, and perceptions of decision mathematics in two sets of questionnaires and one round of follow-up interviews. Together they reported different levels of challenge, mostly positive affective profiles, and a high level of appreciation for the utility of decision mathematics. Using the concept of figured worlds, this article explores further how the students understood the activity contained within the decision mathematics modules, and the extent to which they positioned it as legitimate mathematical practice. The participants' accounts show that the study of decision mathematics not only augmented the students' knowledge of how mathematics might be applied in the world, but for some also worked to extend and reconfigure their perceptions of mathematics as a curriculum discipline.